Does Acute Otitis Media in the First Month of Life Increase the Risk for Recurrent Otitis?. (January 2018) - Megged, Orli; Abdulgany, Suzan; Bar-Meir, Maskit
Acute otitis media (AOM) is a common childhood illness. The aim of this study was to assess whether AOM in the first month of life predicts recurrent AOM (rAOM) in early childhood. The medical records of all neonates with AOM and isolation of bacterial pathogen from middle-ear fluid during 2005-2010 were reviewed. Neonates without AOM admitted during the same period for neonatal fever workup were included as controls. Information regarding rAOM and possible risk factors were collected through a phone interview with the parents. A total of 84 neonates with AOM were enrolled; 25 (30%) had rAOM compared with 8/79 (10%) in the control group. Neonatal AOM increases 4-fold the odds of rAOM later in childhood (odds ratio = 4; 95% CI = 1.44-11.42; P = .008), independent of smoke exposure, numbers of siblings, AOM in siblings, breastfeeding, day care attendance, or use of pacifier. Neonatal AOM is a significant risk factor for rAOM during infancy.